Strategic insights into organ donation: perceptions, attitudes, and the impact of disincentive removal in current and future medical professionals - Arizmendi-Villarreal, Marco A.; Ugalde-Flores, Ana C.; Sanchez-Maldonado, Javier; Flores-Mendoza, Allina P.; Zapata-Chavira, Homero A.; Muñoz-Maldonado, Gerardo E.; Perez-Rodriguez, Edelmiro; Reyna-Sepulveda, Francisco J. (Frontiers in Public Health, 2025)
IntroductionOrgan transplantation is a life-saving intervention for patients with end-stage organ failure, yet donation rates remain critically low in many countries. A better understanding of the medical community’s perceptions and the barriers to donation, especially disincentives for donation, is crucial for improving organ procurement.MethodsWe conducted a cross-sectional, observational study using a 22-item structured survey to assess knowledge, attitudes, and disincentives to organ and tissue donation among 686 participants, including medical students, residents, and healthcare personnel from the Universidad Autónoma de Nuevo León.ResultsMost of the participants (81.6%) were willing to donate organs posthumously, and 72.3% expressed willingness to donate during life. However, 54.4% were unaware that the family had the final decision regarding donation. Common disincentives for living donation included concerns about long-term health impacts (23.9%), risk of chronic kidney disease (21%), and fear of death during nephrectomy (19.5%). Notably, 92% believed living donors should receive social or economic support, without perceiving this as conflicting with altruism. Male sex (OR = 2.06; 95% CI: 1.36–3.10) and lack of prior education on donation (OR = 2.54; 95% CI: 1.68–3.84) were significantly associated with unwillingness to donate (p ≤ 0.001).DiscussionAlthough attitudes toward organ donation are generally favorable among future healthcare professionals, significant knowledge gaps and systemic barriers persist. Implementing structured educational programs, trust-building measures, and policies that remove financial disincentives could strengthen Mexico’s culture of donation and improve transplant outcomes.